Phrase and Clause Usage in Michael Jackson’s Song Lyrics - Muhammad Adi Pratama (Lexicon, 2015)
This research aims to find out the usage of phrase and clause types that are found in Michael Jackson song-lyrics such as Billie Jean, Beat It, Black or White, Dirty Diana, Earth Song, Heal the World, Man in the Mirror, Smooth Criminal, They Don’t Really Care About Us, and Thriller. The phrase and clause types are based on Eastwood’s categories. The phrase is divided into five types: (1) verb phrase, (2) noun phrase, (3) adjective phrase, (4) adverb phrase and (5) prepositional phrase, while the clause is divided into two types, namely main clause and sub clause. There are also four types of sub clause: (1) adverbial clause, (2) conditional clause, (3) noun clause, (4) and relative clause. This categorization can find out the usage of grammatical pattern in the sentence. In the analysis, the findings of phrases and clauses show that the most dominant number are noun phrase (51.94%) and main clause (63.74%).